Pengaruh ROA, ROE, LDR, CAR, Dan NPL Terhadap Harga Saham Perbankan Yang Terdaftar di BEI - Nur Aryanti, Asti; Rahmi, Palupi Permata; Herlina, Listri (Forum Kerjasama Pendidikan Tinggi, 2022)
One of the sectors that has rapid development that support the national economy and have an important role in national development is the banking sector. This research aimed at analyzing the effect of Return on Assets, Return on Equity, Loan Deposit Ratio, Capital Adequacy Ratio, and Non-Performing Loans on banking stock prices listed on the IDX (Case Research of BUMN Banks for the Period 2008 – 2021). This research employed a quantitative method with a descriptive and verification approach. The type of data used were quantitative data. Secondary data, which consisted of data on the annual financial statements of BUMN Banks for the period 2008-2021, were collected using a purposive sampling technique. The analytical method used in this research was multiple linear regression. The t test and F test were carried out to obtain results regarding the effect of the independent variables on the dependent variable. The results showed that partially, Return on Equity (ROE) and Non-Performing Loans (NPL) had a significant effect on stock prices. While the ROA, LDR and CAR variables had no significant effect on stock prices. The test results of the coefficient of determination (R2) showed that the variables Return on Assets, Return on Equity, Loan to Deposit Ratio, Capital Adequacy Ratio, and Non-Performing Loans had an influence on stock prices by 38.60% and the remaining 61.40% was influenced by other external factors.